Contextual determinants of health behaviours in an aboriginal community in Canada: pilot project - Joseph Pamela; Davis A; Miller Ruby; Hill Karen; McCarthy Honey; Banerjee Ananya; Chow Clara; Mente Andrew; Anand Sonia S (BMC, 2012)
Abstract Background Rapid change in food intake, physical activity, and tobacco use in recent decades have contributed to the soaring rates of obesity, type 2 diabetes and cardiovascular disease (CVD) in Aboriginal populations living in Canada. The nature and influence of contextual factors on Aboriginal health behaviours are not well characterized. Methods To describe the contextual determinants of health behaviours associated with cardiovascular risk factors on the Six Nations reserve, including the built environment, access and affordability of healthy foods, and the use of tobacco. In this cross-sectional study, 63 adults from the Six Nations Reserve completed the modified Neighbourhood Environment Walkability Scale (NEWS), questionnaire assessing food access and availability, tobacco pricing and availability, and the Environmental Profile of Community Health (EPOCH) tool. Results The structured environment of Six Nations Reserve scored low for walkability, street connectivity, aesthetics, safety, and access to walking and cycling facilities. All participants purchased groceries off-reserve, although fresh fruits and vegetables were reported to be available and affordable both on and off-reserve. On average $151/week is spent on groceries per family. Ninety percent of individuals report tobacco use is a problem in the community. Tobacco is easily accessible for children and youth, and only three percent of community members would accept increased tobacco taxation as a strategy to reduce tobacco access. Conclusions The built environment, access and affordability of healthy food and tobacco on the Six Nations Reserve are not perceived favourably. Modification of these contextual factors described here may reduce adverse health behaviours in the community.